Serum interleukin-1beta and tumor necrosis factor-alpha in febrile seizures: is there a link? - Abolfazl Mahyar; Parviz Ayazi; Reza Orangpour; Mohammad Mahdi Daneshi-Kohan; Mohammad Reza Sarokhani; Amir Javadi; Morteza Habibi; Mousa Talebi-Bakhshayesh (Korean Pediatric Society, 2014)
PurposeFebrile seizures are induced by fever and are the most common type of seizures in children. Although numerous studies have been performed on febrile seizures, their pathophysiology remains unclear. Recent studies have shown that cytokines may play a role in the pathogenesis of febrile seizures. The present study was conducted to identify potential links between serum interleukin-1beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and febrile seizures.MethodsNinety-two patients with simple or complex febrile seizures (46 patients per seizure type), and 46 controls with comparable age, sex, and severity of temperature were enrolled.ResultsThe median concentrations of serum IL-1β in the simple, complex febrile seizure, and control groups were 0.05, 0.1, and 0.67 pg/mL, respectively (P=0.001). Moreover, the median concentrations of TNF-α in the simple, complex febrile seizure, and control groups were 2.5, 1, and 61.5 pg/mL, respectively (P=0.001). Furthermore, there were significant differences between the case groups in serum IL-1β and TNF-α levels (P<0.05).ConclusionUnlike previous studies, our study does not support the hypothesis that increased IL-1β and TNF-α production is involved in the pathogenesis of febrile seizures.